Analysis of Saving Habits Among Students: A Case Study of Uganda Christian University - Divine Bagoso Nabini (Uganda Christian University, 2023)
This study examines the saving habits of students at Uganda Christian University (UCU) to gain insights into their financial behaviors and attitudes towards saving. The research employs a mixed-methods approach, combining surveys and interviews to collect data from a representative sample of UCU students. The study investigates factors influencing students' saving behavior, their financial goals, and the impact of financial education on their saving habits. The findings reveal that a significant proportion of UCU students have limited savings, with most citing income constraints as the primary barrier to saving. Additionally, the study identifies a positive correlation between financial education and improved saving habits among students. Factors such as parental influence, peer pressure, and financial literacy are shown to play pivotal roles in shaping the saving behavior of students. The research concludes by emphasizing the importance of financial education programs tailored to the specific needs of students at UCU. It also suggests strategies to enhance saving habits among students, such as promoting financial literacy initiatives, creating a culture of saving, and providing access to financial resources that cater to the unique financial challenges faced by students. Ultimately, this study contributes to the understanding of saving habits among university students in Uganda, offering valuable insights for educators, policymakers, and financial institutions aiming to support young adults in building healthy financial futures.
This is a dissertation.